Investigating the Ability to Mask Dental Discoloration by CAD/CAM Bleach Shade Ceramics in Different Thicknesses - Shervin Reybod; Fariba Ezoji; Ghazaleh Ahmadizenouz; Behnaz Esmaeili (Clinical and Experimental Dental Research)
ABSTRACT Objectives The initial color of a ceramic restoration is determined by the background color. Dental ceramics are great at masking a variety of stains, which helps achieve a natural and beautiful smile. A recent study delved into the effectiveness of CAD/CAM bleach shade ceramics of varying thicknesses in concealing dental discoloration. Material and Methods In this laboratory research, ceramic samples including feldspathic ceramics, lithium silicate ceramics, and zirconia ceramics of varying thicknesses were used. Each type of ceramic had a thickness of 0.5, 1.0, 1.5, and 2.0 mm, with dimensions of 7 × 7 mm (n = 10). Backgrounds of C4 and A2 color porcelain were used. To evaluate color coverage, ceramic pieces were placed on the C4 and A2 porcelain backgrounds, and the Vita spectrophotometer was used to calculate the L*a*b* parameters and color difference (ΔE00). A ΔE00 value of ≤ 1.8 was considered clinically acceptable. The data was analyzed using two‐way and one‐way analysis of variance tests, and pairwise comparisons of groups were performed using Tukey's test. Results The research revealed that both the thickness and type of ceramic material significantly influenced the color changes of the samples, with their interaction also playing a crucial role (all three: p < 0.001). Zirconia demonstrated superior color masking performance on the C4 substrate at 0.5 and 1.0 mm thicknesses. The masking ability of ceramics varied at 0.5, 1.0, and 1.5 mm but notably improved at a thickness of 2.0 mm. Conclusions Zirconia generally demonstrated superior masking ability across all thicknesses, while other ceramics exhibited commendable performance only at 1.5 and 2.0 mm thicknesses. Nevertheless, augmenting the thickness of ceramic restorations amplified their masking capability.